KERAGAAN DAN PENGEMBANGAN AGRIBISNIS KOPI ROBUSTA DI PROVINSI LAMPUNG (Studi Kasus : Kab Tanggamus) - valeriana darwis; Yonas Hangga Saputra; Chairul Muslim (Politeknik Negeri Lampung, 2020)
Lampung Province is one of the Robusta coffee agribusiness centers that is included in the development area of ​​the coffee area contained in the Decree of the Minister of Agriculture No. 472 of 2018. Based on this stipulation, this paper aims to determine the production system, maintenance costs and supply chain in Lampung Province. The survey was conducted in July 2019 with data collection methods through FGD and direct interviews with farmers using a questionnaire. From the results of a qualitative descriptive analysis and maintenance cost, it was found that the Robusta coffee agribusiness in Lampung Province experienced positive growth. This is represented by an increase in coffee selling price of 0.39% / year, planting area of ​​0.33% / year and production of 0.09% / year. But in terms of productivity, respondents' farmers only produce 593 kg / year or still low compared to national productivity of 656 kg / year and Lampung province productivity of 800 kg / year. The low productivity of respondent farmers was caused by: (i) lack of motivation to maintain because the maintenance costs per kg (Rp. 4,013) were lower than the selling price of coffee (Rp. 18,000); (ii) the age of the plant is old and (iii) it is not the main crop. Coffee agribusiness in Lampung Province can still be improved by: (i) increasing productivity through the application of coffee-based cultivation; (ii) making demonstration plots at farmer locations as an effort to disseminate research results from the Ministry of Research and Development; (iii) rebuilding institutions especially in overcoming the problems of production, marketing and processing of products and (iv) making partnerships with traders or roasteries so that farmers no longer need to sell as origin seeds